2021
DOI: 10.3389/fimmu.2021.654540
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells: Versatile Players in Renal Transplantation

Abstract: Dendritic cells (DCs) induce and regulate adaptive immunity through migrating and maturing in the kidney. In this procedure, they can adopt different phenotypes—rejection-associated DCs promote acute or chronic injury renal grafts while tolerogenic DCs suppress the overwhelmed inflammation preventing damage to renal functionality. All the subsets interact with effector T cells and regulatory T cells (Tregs) stimulated by the ischemia–reperfusion procedure, although the classification corresponding to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 208 publications
(225 reference statements)
0
18
0
Order By: Relevance
“…The most efficient antigen presenting cells (APCs) in activating T cells and initiating immune tolerance are the DCs. Based on different surface markers, DCs are generally divided into three subsets: (i) DCs involved in ischemia-reperfusion injury (IRI) and expressing C1d, CD8α, CD11c, CD40, CD45, CD54 (ICAM), CD80, CD86, MHC-II, and TNFα, but are negative for CD4 and CD205 ( 101 ); when activated by antigens released during ischemia-reperfusion, these DCs can trigger both cellular and antibody-mediated rejection, resulting in harmful antibodies secretion by activated B cells and killing of donor cells by cytotoxic T cells ( 102 ); (ii) rejection-related DCs, promoting acute and chronic rejection via different interactions with T cells and are characterized by the expression of CD11c, MHC-II, CD1c and FcϵRI ( 103 ); (iii) tolerogenic DCs, suppressing the rejection process by dampening the T cell effector functions and promoting T regulatory cells (Tregs) activity; these DCs express significantly lower levels of MHC, T cell co-stimulatory molecules, such as CD40, and CD80/86, and inhibitory ligands, such as programmed death ligand-1 (PD-L1) and death-inducing ligands, reflecting their non-phagocytic profile ( 104 , 105 ). In response to specific signals such as DAMPs, host DCs can acquire a rejection-related phenotype, which can further evolve towards a tolerogenic phenotype upon treatment with rapamycin, IL-10, vitamin D, or low-dose granulocyte-macrophage colony-stimulation factor (GM-CSF).…”
Section: Mechanism Of Xenograft Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most efficient antigen presenting cells (APCs) in activating T cells and initiating immune tolerance are the DCs. Based on different surface markers, DCs are generally divided into three subsets: (i) DCs involved in ischemia-reperfusion injury (IRI) and expressing C1d, CD8α, CD11c, CD40, CD45, CD54 (ICAM), CD80, CD86, MHC-II, and TNFα, but are negative for CD4 and CD205 ( 101 ); when activated by antigens released during ischemia-reperfusion, these DCs can trigger both cellular and antibody-mediated rejection, resulting in harmful antibodies secretion by activated B cells and killing of donor cells by cytotoxic T cells ( 102 ); (ii) rejection-related DCs, promoting acute and chronic rejection via different interactions with T cells and are characterized by the expression of CD11c, MHC-II, CD1c and FcϵRI ( 103 ); (iii) tolerogenic DCs, suppressing the rejection process by dampening the T cell effector functions and promoting T regulatory cells (Tregs) activity; these DCs express significantly lower levels of MHC, T cell co-stimulatory molecules, such as CD40, and CD80/86, and inhibitory ligands, such as programmed death ligand-1 (PD-L1) and death-inducing ligands, reflecting their non-phagocytic profile ( 104 , 105 ). In response to specific signals such as DAMPs, host DCs can acquire a rejection-related phenotype, which can further evolve towards a tolerogenic phenotype upon treatment with rapamycin, IL-10, vitamin D, or low-dose granulocyte-macrophage colony-stimulation factor (GM-CSF).…”
Section: Mechanism Of Xenograft Rejectionmentioning
confidence: 99%
“…In response to specific signals such as DAMPs, host DCs can acquire a rejection-related phenotype, which can further evolve towards a tolerogenic phenotype upon treatment with rapamycin, IL-10, vitamin D, or low-dose granulocyte-macrophage colony-stimulation factor (GM-CSF). Tolerogenic DCs reduce CD4+ T cell activation and impair CD8+ T cell functions, which helps suppressing graft rejection ( 102 ). Manna et al.…”
Section: Mechanism Of Xenograft Rejectionmentioning
confidence: 99%
“…Dendritic cells (DCs), which develop from bone marrow-derived hematopoietic stem cells, 27 , 28 are a subset of antigen-presenting cells. They use pattern recognition receptors to initiate and regulate adaptive immune responses.…”
Section: Brief Primer On Immune Cell Biologymentioning
confidence: 99%
“…Studies have shown that DCs induce and maintain immune responses through migration and maturation in the kidney ( 37 ). DCs, although rarely present in normal kidneys, are significantly increased in chronic kidney disease (CKD) and diabetic nephropathy (DN) ( 38 ).…”
Section: Renal Microenvironmentmentioning
confidence: 99%
“…Studies have shown that DCs induce and maintain immune responses through migration and maturation in the kidney (37).…”
Section: Dendritic Cellsmentioning
confidence: 99%